FRAKSI ETANOL, KLOROFORM, DAN N-HEKSAN BUNGA KAMBOJA PUTIH (Plumeria acuminata L.) SEBAGAI ANTIBAKTERI TERHADAP Escherichia coli dan Staphylococcus aureus DENGANBIOAUTOGRAFI - Yuli Wahyu Trimulyani (JFL : Jurnal Farmasi Lampung, 2019)
Frangipani flowers (Plumeria acuminata L.) Flower is one of the plants that has antibacterial properties. Compounds that act as antibacterial are flavonoids and tannins. The purpose of this study was to prove the antibacterial activity of ethanol, chloroform, and n-hexane fractions of Frangipani flowers (Plumeria acuminata L.) flower as antibacterial against E. coli and S. aureus with Bioautography.The process of extracting plumeria acuminata L. flowers was carried out by maceration method using 70% ethanol. The extract was continued with the fractionation process with ethanol, n-hexane and chloroform solvents. Antibacterial activity testing using the well method with concentrations of 20%, 40%, 60%, 80%, 100%, positive chloramphenicol control, and negative aquadest control. The compound content test used the Thin Layer Chromatography (TLC) method with the mobile phase of chloroform: methanol: water (2:5:3) (v/v).Bioautography test using the contact method, namely the elution TLC plate, was placed on the NA medium containing a bacterial suspension for 3 hours. The biggest antibacterial test results of ethanol fraction of plumeria acuminata L. flowers were at a concentration of 100% with a diameter of inhibition zone of 13.55 mm in E. coli while 14.15 mm S. aureus. The results of TLC showed the presence of flavonoids with a price of Rf 0.70 and tannin at a price of Rf 0.68. Bioautography results showed a inhibition zone with a price of Rf 0.70 in E. coli and S. aureus which are flavonoid compounds. Based on the results of the research that has been done it can be concluded that the ethanol fraction of white frangipani flowers has antibacterial activity against E.coli and S. aureus, while the chloroform fraction and n-hexane fraction do not have antibacterial activity. The active compounds that act as antibacterial are flavonoids and tannin, but the ones that provide antibacterial effects are flavonoids with an Rf value of 0.70. Keywords: Bioautography,Escherichiacoli, Frangipani flowers, Staphylococcusaureus, TLC